Dynamic changes of genomic methylation profiles at different growth stages in Chinese Tan sheep - Yufang Liu; Qiao Xu; Xiaolong Kang; Kejun Wang; Jve Wang; Dengzhen Feng; Ying Bai; Meiying Fang (Journal of Animal Science and Biotechnology, 2021)
Abstract Background Tan sheep, an important local sheep breed in China, is famous for their fur quality. One-month-old Tan sheep have white, curly hair with beautiful flower spikes, commonly known as “nine bends”, which has high economic value. However, the “nine bends” characteristic gradually disappears with age; consequently, the economic value of the Tan sheep decreases. Age-related changes in DNA methylation have been reported and may be responsible for age-induced changes in gene expression. Until now, no genome-wide surveys have been conducted to identify potential DNA methylation sites involved in different sheep growth stages. In this study we investigated the dynamic changes of genome-wide DNA methylation profiles in Tan sheep using DNA from skin and deep whole-genome bisulfite sequencing, and compared the DNA methylation levels at three different growth stages: 1, 24, and 48 months old (mon1, mon24, and mon48, respectively). Results In this study, 11 skin samples from three growth stages (four for mon1, four for mon24, and three for mon48) were used for DNA methylation analysis and gene expression profiling. There were 52, 288 and 236 differentially methylated genes (DMGs) identified between mon1 and mon24, mon1 and mon48, and mon24 and mon48, respectively. Of the differentially methylated regions, 1.11%, 7.61%, and 7.65% were in the promoter in mon1 vs. mon24, mon24 vs. mon48, and mon1 vs. mon48, respectively. DMGs were enriched in the MAPK and WNT signaling pathways, which are related to age growth and hair follicle morphogenesis processes. There were 51 DMGs associated with age growth and curly fleece formation. Four DMGs between mon1 and mon48 (KRT71, CD44, ROR2 and ZDHHC13) were further validated by bisulfite sequencing. Conclusions This study revealed dynamic changes in the genomic methylation profiles of mon1, mon24, and mon48 sheep, and the percentages of methylated cytosines were 3.38%, 2.85% and 4.17%, respectively. Of the DMGs, KRT71 and CD44 were highly methylated in mon1, and ROR2 and ZDHHC13 were highly methylated in mon48. These findings provide foundational information that may be used to develop strategies for potentially retaining the lamb fur and thus improving the economic value of Tan sheep.